Atypical case of Lemierre's syndrome secondary to cellulitis of the orofacial region - Vishal N. Mepani; Bhavin G. Visavadia (Elsevier, 2025)
Lemierre's syndrome is a rare condition associated with infection of the oropharynx. We present an atypical case in a young healthy female who developed the condition secondary to a skin infection of the lip and chin. She also developed sepsis and chest pain. She was commenced on broad-spectrum antibiotics early and was fortunate to avoid aggressive surgical treatment. This case highlights the need for clinicians to consider this rare condition in addition to recognising its manifestations.